Soft tissue-related injuries sustained following volcanic eruptions: An integrative review. Issue 7 (November 2022) - Beylin, Dmitry; Mantal, Ortal; Haik, Josef; Kornhaber, Rachel; Cleary, Michelle; Neil, Amanda; Harats, Moti
Highlights: Volcanic eruptions can cause serious life-threatening injuries. Limited research exists on immediate/short-term health consequences post eruptions. Knowledge of expected soft tissue-related injuries can inform emergency management. Abstract: Background: The contribution of various volcanic phenomena to immediate soft tissue injury types has received limited attention challenging emergency management planning. This integrative review sought to investigate the immediate types of soft tissue-related injury sustained following volcanic eruptions. Methods: A systematic search was conducted in January 2020 across EMBASE, PubMed, and Scopus databases. 718 articles were retrieved, and 15 studies met the final inclusion criteria. Results: Injuries acquired, and health impacts were categorized by onset-direct/indirect or immediate/delayed. Health concerns following an eruption were categorised: (1) respiratory; (2) ocular; and (3) skin, including deep tissues. Respiratory concerns were attributed to ashfall, volcanic gases and pyroclastic density currents; most ocular injuries to ashfall; and skin/deep tissues to pyroclastic density currents and mudflows. Conclusions: Volcanic eruptions simultaneously present multiple hazards with immediate/short term health consequences across three major levels ( i.e., respiratory, ocular, and skin, including deep tissues). Hazard(s) differ by time of onset and associated mostly with the eruptive phenomena. Understanding local volcanic phenomenon is essential to assisting health personnel provide informed and timely care.